Rule-Based Algorithm pada Simulasi Smart Farming Berbasis Wokwi dan Firebase - Rahayuda, I Gede Surya; Santiari, Ni Putu Linda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025DO - 10.24843/JLK.2025.v13.i03.p16, 2025)
This study focuses on developing a smart farming system utilizing Wokwi, Firebase, and JavaScript with a Rule-Based algorithm to automate irrigation, heating, and alarm functions based on sensor data. The system is designed to enhance agricultural efficiency by integrating real-time monitoring and control via a web-based platform. Evaluation using a confusion matrix resulted in perfect accuracy, which is likely due to the use of simulation tools. However, these results may differ in real-world applications. Future research could explore implementing this system in actual environments, particularly for small plants or terrariums, given the compact size and low power consumption of IoT devices. Testing on plants such as cacti, succulents, or carnivorous plants like Nepenthes can provide further insights into its practical effectiveness under real conditions. Keywords : Wokwi, Firebase, JavaScript, Rule-Based Algorithm, Smart Farming